2009
DOI: 10.1016/j.otohns.2008.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillectomy for obstructive sleep apnea in obese children: A meta‐analysis

Abstract: T&A improves but does not resolve OSA in the majority of obese children. The efficacy and role of additional therapeutic options require more study. The high incidence of obesity in children makes this a public health priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(165 citation statements)
references
References 43 publications
2
154
2
7
Order By: Relevance
“…38 In CHAT, obese children in both groups had lower rates of normalization of polysomnographic findings than did nonobese children, although the prevalence of residual obstructive sleep apnea syndrome in the obese group postoperatively (33% of children) was lower than has been reported in some studies, 5,38,39 possibly because CHAT was limited to preadolescents and excluded extremely obese patients. Polysomnographic findings, as well as symptoms and behavior, improved more with early adenotonsillectomy than with watchful waiting, however, in both obese and nonobese children.…”
Section: Discussionmentioning
confidence: 83%
“…38 In CHAT, obese children in both groups had lower rates of normalization of polysomnographic findings than did nonobese children, although the prevalence of residual obstructive sleep apnea syndrome in the obese group postoperatively (33% of children) was lower than has been reported in some studies, 5,38,39 possibly because CHAT was limited to preadolescents and excluded extremely obese patients. Polysomnographic findings, as well as symptoms and behavior, improved more with early adenotonsillectomy than with watchful waiting, however, in both obese and nonobese children.…”
Section: Discussionmentioning
confidence: 83%
“…Our success rate of treating SDB with weight loss of 71% stresses the important role of adiposity in the pathogenesis of SDB in childhood obesity. When comparing this treatment success rate with literature regarding adenotonsillectomy, we can conclude that weight loss might be more effective in treating SDB in a highly morbid obese population (10)(11)(12). Weight loss treatment can therefore be considered as a first line treatment, but based on our data of tonsillar hypertrophy in residual SDB the combination of both adenotonsillectomy or pharmacological treatment and weight loss treatment in selected patients needs to be studied.…”
Section: Discussionmentioning
confidence: 91%
“…Another retrospective review of 26 morbidly obese patients, all of whom were sent to the ICU after AT as per routine, found that 14 patients (54%) had an uncomplicated postoperative course, and 12 (45%) required respiratory intervention, including 1 requiring intubation and 2 requiring BPAP. 196 Costa and Mitchell 131 evaluated the response to AT in a meta-analysis of 4 studies that included 110 obese children who had OSAS (level III). They found that OSAS improved but did not resolve after AT, with 88% of children having an AHI >1/hour and 51% of children having an AHI >5/hour postoperatively.…”
Section: Surgical Treatment Of Osas In the Obese Childmentioning
confidence: 99%